The teachers' extent of utilizing teaching methods for teaching basic technology - Obielodan, Omotayo Olabo; Onojah, Amos Ochayi; Onojah, Adenike Aderogba; Alabi, Odunayo Sunday; Alimi, Emmanuel Adebayo (Univeritas Papua, 2021)
The teaching method which teachers adopt for instruction could aggravate students’ performance if successfully employed. However, its use may not be optimum as expected. This study investigated the extent of utilization of teaching methods used for teaching basic technology and the influence of gender on teachers’ extent of utilizing teaching methods to teach basic technology. The study adopted a descriptive research design. One hundred twenty-two basic technology teachers in Nigeria were purposively sampled. The findings of this study were that question and answer, discussion, inquiry, and discovery, field trip, and project and presentation teaching methods are always employed by basic technology teachers in teaching while role-playing, game, and simulation teaching method are moderately utilized for teaching. Also, there was a significant difference between male and female teachers’ extent of utilizing teaching methods to teach basic technology in favor of the male basic technology teachers. The study concluded that appropriate use of teachers’ desired teaching methods could influence instructional delivery. It was thus recommended that educational institutions should organize conferences, seminars, training, and workshops for basic technology teachers on the use of effective teaching methods.